Utilization of 19F MRI for Identification of Iraq-Afghanistan War Lung Injury. - Mammarappallil, Joseph G; Shofer, Scott; Carraway, Martha S; Tucker, Jesse; Womack, Samantha; Ainslie, Maureen; Charles, H Cecil (Military Medicine)
Introduction: There is mounting evidence of respiratory problems related to military service in the Middle East in the past two decades due to environmental exposures during deployment (eg, sand storms and burn pits). This pilot study tests the hypothesis that regional lung function in subjects with prior deployment in Iraq and/or Afghanistan with suspected War Lung Injury (WLI) would be worse than subjects with normal lung function.Materials and Methods: Five subjects meeting the inclusion and exclusion criteria were recruited for this pilot study. All subjects underwent spirometry, high-resolution chest computed tomography imaging, and 19F MRI.Results: While the WLI subjects had normal pulmonary function tests and normal high-resolution chest computed tomography evaluations, their regional lung function from 19F MRI was abnormal with compartments with poor function showing slower filling time constants for ventilation. The scans of suspected WLI subjects show higher fractional lung volume with slow filling compartments similar to patients with chronic obstructive pulmonary disease in contrast to normal subjects.Conclusions: This is consistent with our premise that WLI results in abnormal lung function and reflects small airways dysfunction and suggests that we may be able to provide a more sensitive tool for evaluation of WLI suspected cases.